Work-family conflict and occupational stress as correlates of life satisfaction among staff of Oyo state civil service (2016)
There is limited research on civil servants and their experiences of work-family conflict and life satisfaction. The goals of the present study were to examine the relationship between work-family conflict (work-to-family conflict and family-to work conflict) and life satisfaction, the relationship between work-family conflict and domain-specific satisfactions (family satisfaction and work satisfaction), among a sample of civil servants. The study utilized ex-post facto design with the use of a structured questionnaire. Two hundred and eighty-four (284) employees of Oyo state civil service participated in the study, yielding a return rate of 94.7%. A total of134 (47.2%) males and 150 (52.8%) females participated in the study. Their ages ranged between 18 and 58 with mean age of 37.9 and standard deviation of 11.2. The instrument used was closed-ended questionnaire divided into five sections. This comprised demographic variables, work-family conflict, occupational stress and life satisfaction. Five hypotheses were tested. The result indicated a significant negative relationship between work-family conflict and life satisfaction (r--0.310, p<.01). Occupational stress also correlated negatively with life satisfaction (r--0.251, p<.01). The result of the regression analysis indicated that work-family conflict and occupational stress jointly predicted life satisfaction [F (2,281)-20.169; R2=0.126, p<0.001 ] accounting for 12.6% variance. Also, there was no gender difference in the experience of life satisfaction [t(282) = -0.093; p> 0.05]. Finally, age, sex, years of experience, level of education, religion and marital status did not predict life satisfaction among civil servants [F(6,277)-2.698; R2-0.095 p<0.01 ] accounting for about 9.5 variance. Based on the findings, conclusions were made, and it was recommended that different policies and strategies are needed for the people at different type of jobs and at different stages of their career. As one of the largest employer of any country, government should introduce appropriate policies in the area of work-family balance